Fifty years of top-class table tennis world ranking - Malagoli Lanzoni, I.; Di Michele, R.; Semprini, G. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The aim of this study was to analyse of some aspects of the world table tennis rankings in order to better understand the historical and technical evolution of this sport. One world ranking for every year from 1967 to 2017 was examined by identifying the first 10 male (M) and female (F) players. For each player the, handedness (left- or right-handed), grip (classic or pen-holder), style of play (offensive or defensive), and nationality, were recorded. All data are presented as percentages. Left-handed are overrepresented (M: 25.4; F: 22.6) with respect to the normal population (10-13%). The classic grip is the most used (M: 72.8; F: 72.5). In M players, a slight increase was observed while in F since 1985 until today the classic grip showed an important increase. The predominant playing style is offensive (M: 93.4; F: 88.9) with an increasing trend in M and F. In M the most represented nation is China (39.6) followed by Sweden (12.8), Japan (7.8), Korea (5.1), Germany (4.9), Yugoslavia (4.3). In F: China (50.4), Japan (8.8), Korea (7.3), PRK (4.6), USSR (3.1), Singapore (2.9), and Hungary (2.4). In the last 50 years the Asian athletes have dominated the world rankings (M: 56.5; F: 50.4). This domination started in 2003 for M, after a period of substantial balance with Europeans and for F it constantly increases since 1971. Asians are followed by Europeans (M: 43.3; F: 18.8) and Americans (M: 0.2; F: 0.1).